2006
DOI: 10.1210/me.2005-0392
|View full text |Cite
|
Sign up to set email alerts
|

The Genes Induced by Signal Transducer and Activators of Transcription (STAT)3 and STAT5 in Mammary Epithelial Cells Define the Roles of these STATs in Mammary Development

Abstract: Prolactin and leukemia inhibitory factor (LIF) have different roles in the adult mammary gland, which are mediated in part by the signal transducers and activators of transcription (STAT)5 and STAT3. In vivo studies have shown that STAT5 contributes to prolactin-dependent lobuloalveolar development and lactation whereas STAT3 mediates LIF-dependent epithelial apoptosis during postlactational involution. To understand the molecular basis of these STAT-dependent pathways, we demonstrate the ligand-independent ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
109
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(122 citation statements)
references
References 38 publications
11
109
1
1
Order By: Relevance
“…We have previously reported that expression of the NF-kB cofactor Bcl3 is dependent on Stat3 in mammary epithelial cells (5). This was confirmed for both Bcl3 mRNA and protein levels in normal mammary tissues ( Fig.…”
Section: Bcl3 Is Elevated In Erbb2-positive Mammary Tumor Cells But Dsupporting
confidence: 73%
See 2 more Smart Citations
“…We have previously reported that expression of the NF-kB cofactor Bcl3 is dependent on Stat3 in mammary epithelial cells (5). This was confirmed for both Bcl3 mRNA and protein levels in normal mammary tissues ( Fig.…”
Section: Bcl3 Is Elevated In Erbb2-positive Mammary Tumor Cells But Dsupporting
confidence: 73%
“…4). Previously, we had identified a panel of genes from murine mammary epithelial cells that were responsive to Stat3 (5). One of these Stat3-responsive genes, Bcl3, is a proto-oncogene originally described in B-cell lymphomas that has previously been shown to be constitutively expressed in a small study of breast cancer tissues (6,7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study also revealed that the activation of STAT3 was inhibited during mammary gland involution in the absence of Nucling, resulting in suppressed expression of C/EBP␦ mRNA, which is induced by STAT3 signaling (36). C/EBP␦ is known to be important in the apoptotic response in mammary glands as well as in diminished involution in C/EBP␦-deficient mice (37).…”
Section: Discussionsupporting
confidence: 52%
“…3T3-L1 cells were treated with butein for 12 and 24 h, and the expression of several known STAT3-regulated genes was analyzed. STAT3 is known to regulate several target genes, including KLF5 , P53 , CycD1 , C/EBP ␦ , and STAT3 ( 30 ). The known STAT3-downregulated genes KLF5 and P53 were induced by butein.…”
Section: Stat3 Mediates the Anti-adipogenic Effects Of Buteinmentioning
confidence: 99%